Evaluating the Use of Discourse Markers in Selected English Education Journal Articles - Egi Raputri; Hendi Pratama; Rudi Hartono (English Education Journal, 2022)
Considering the important roles of discourse markers in writing academic purposes, the researchers evaluate the use of discourse markers in English Education Journal articles. This research aims to find out the types of discourse markers precisely contrastive, elaborative and inferential discourse markers, and the errors in using those expressions. This research uses a qualitative research design with the data from written language especially the journal articles published by English Education Journal (EEJ). Thus, specifically this research employs content analysis. There were twenty journal articles analyzed. They represented their volume especially there are four volumes in 2020. The findings of this research demonstrated that all of the research data applied those types of discourse markers. The type of elaborative discourse markers were the first type used by the writers. It is the frequently used by the writers in the journal articles. In this case, it used in 890 times. The expression frequently used is and. Meanwhile, the errors in using discourse markers in the journal articles occurred in 17 times. Here, the wrong relation category as the commonly applied in 7 times. These findings inform us to improve our awareness in applying those expressions. Thus, it can be concluded that the discourse markers is required in creating journal articles. Therefore, the writers have to concern regarding to the categories of errors in using discourse markers for avoiding inappropriateness.